Functional conformer of c‐Myb DNA‐binding domain revealed by variable temperature studies. (29th September 2015) - Inaba, Satomi; Maeno, Akihiro; Sakurai, Kazumasa; Narayanan, Sunilkumar Puthenpurackal; Ikegami, Takahisa; Akasaka, Kazuyuki; Oda, Masayuki
Abstract : The conformational fluctuation in the minimum DNA‐binding domain of c‐Myb, repeats 2 and 3 (R2R3), was studied under closely physiological conditions. A global unfolding transition, involving both the main chain and the side chains, was found to take place at the approximate temperature range 30–70 °C, with a transition temperature of approximately 50 °C. In addition, the observation of simultaneous shift change and broadening of NMR signals in both 1 H one‐dimensional and 15 N/ 1 H two‐dimensional NMR spectra indicated the occurrence of locally fluctuating state at physiological temperature. In the wild‐type protein containing a cavity in R2, the local fluctuation of R2 is more prominent than that of R3, whereas it is suppressed in the cavity‐filled mutant, V103L. This indicates that the cavity in R2 contributes significantly to the conformational instability and the transition into the locally fluctuating state. For the wild‐type R2R3 protein, the more dynamic conformer is estimated to be present to some extent at 37 °C and is likely beneficial for its biological function: DNA‐binding. This result is in agreement with the concept of an excited‐state conformer that exists in equilibrium with the dominant ground‐state conformer and acts as the functional conformer of the protein. From the findings of the present study, it appears that the tandem repeats of two small domains with no disulfide bonds and with a destabilizing cavity function as the evolutionary strategy of the wide‐type c‐Myb DNA‐binding domain to produce an appropriate fraction of the locally fluctuating state at 37 °C, which is more amenable to DNA‐binding. Database: Chemical shifts and peak lists have been deposited in the Biological Magnetic Resonance Bank under entries 11584 and 11585. Abstract : For the minimum DNA‐binding domain of c‐Myb, R2R3, containing a cavity in R2, the unfolded conformer is estimated to be present at 10% at 37°C, and is likely to be beneficial to the biological function, DNA‐binding. Extensive conformational fluctuations within the folded manifold of R2R3 were found to be activated at physiological temperatures.